Just Help Me: A Research Poem by Black Mothers. (December 2022) - Parker, Amittia
This poem was created using the findings in a constructivist grounded theory study on Black maternal mental health and supports for mental health. During in-depth interviews, Black mothers in a midwestern metropolitan context shared their experiences with their mental health, strengths, struggles, supports, and solutions. This author—a Black mother from the same community—created this poem using the participants' spoken words to radically center their voices and expertise. This poem is a stand-alone creative tool to inspire critical self-reflection and action to enhance existing supports and create better support for Black mothers.